1995
DOI: 10.2527/1995.7351239x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of feed intake level on comparative ruminal and total tract digestion of dry-rolled and steam-flaked corn

Abstract: Four Holstein steers (208 kg) with "T" cannulas in the rumen and proximal duodenum were used in a 4 x 4 Latin square design experiment to evaluate the interaction of feed intake level on comparative ruminal and total tract digestion of dry-rolled and steam-flaked corn. The basal diet contained (DM basis) 6% alfalfa hay, 6% sudangrass hay, 75% corn, 2% yellow grease, 5% cottonseed meal, 3% cane molasses, and 3% supplement. The corn portion of the diet was provided as either dry-rolled (density = .54 kg/L) or st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
47
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 26 publications
12
47
0
3
Order By: Relevance
“…However, several trials have been published, primarily from one laboratory, which compare DRC and SFC. Reported BCP flows range from similar (Zinn et al, 1995), to 13% greater (Barajas and Zinn, 1998), 28% greater (Zinn, 1990), and 31% greater for steers fed SFC compared with DRC-based diets. Bacterial CP efficiencies were similar between SFC and DRC in all of these trials except Zinn et al (1995), which reported a 14.2% lower BCP efficiency for SFC compared with DRC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several trials have been published, primarily from one laboratory, which compare DRC and SFC. Reported BCP flows range from similar (Zinn et al, 1995), to 13% greater (Barajas and Zinn, 1998), 28% greater (Zinn, 1990), and 31% greater for steers fed SFC compared with DRC-based diets. Bacterial CP efficiencies were similar between SFC and DRC in all of these trials except Zinn et al (1995), which reported a 14.2% lower BCP efficiency for SFC compared with DRC.…”
Section: Discussionmentioning
confidence: 99%
“…Reported BCP flows range from similar (Zinn et al, 1995), to 13% greater (Barajas and Zinn, 1998), 28% greater (Zinn, 1990), and 31% greater for steers fed SFC compared with DRC-based diets. Bacterial CP efficiencies were similar between SFC and DRC in all of these trials except Zinn et al (1995), which reported a 14.2% lower BCP efficiency for SFC compared with DRC. In our trial, steers fed SFC had greater (P < 0.05) ruminal OM degradation compared with DRC, but the bacterial N efficiency was numerically 6% lower resulting in equal BCP flow from the rumen.…”
Section: Discussionmentioning
confidence: 99%
“…O indicador externo utilizado para determinação da digestibilidade no trato digestivo total foi o óxido de cromo, colocado no rúmen através da cânula, na quantidade de 50 g/d em duas doses, do 5º ao 14º dia de cada período, considerando a quantidade como 0,4% da ingestão de matéria seca, em conformidade com Zinn et al (1995). Amostras das fezes foram colhidas nos quatro primeiros dias do período de colheita de dados, em intervalos de quatro horas, atrasando-se o horário em uma hora por dia para se ter amostragens em cada hora do dia.…”
Section: Experimento 2 Experimento 2 Experimento 2 Experimentounclassified
“…Sindt et al [79] examined the impact of grain processing on ruminal fermentation and found that decreasing flake density from 360 or 310 g/L increased microbial efficiency (P < 0.05) and tended to increase microbial nitrogen flow to the duodenum (P < 0.10). Zinn et al [80] studied the impact of grain processing and dry matter intake on ruminal fermentation and found that steam-flaking corn increased (P < 0.05) ruminal digestion of organic matter and starch. Ruminal pH levels were lower and molar proportions of acetate were higher in steers with greater dry matter intake and for steers fed steam-flaked corn diets compared with steers fed dry-rolled corn (P < 0.05).…”
Section: Microbial Fermentation In the Rumenmentioning
confidence: 99%